Conjoint Analysis of Consumers’ Preference towards Packaged Milk - Arora, Amit Kumar; Gupta, Vijay Prakash (Indian Journal of Marketing, 2020)
Consumption of milk is considered as an essential set of choices in our Indian food habits, due to which we attempted to find out the consumer preference of milk towards packaged milk and conducted a conjoint analysis of the factors influencing the purchase decision of packaged milk. The research was carried out with a sample of common individuals/households residing in the Ghaziabad region. We collected the data using a structured questionnaire by using convenient random sampling technique. One-sample t-test was used to ascertain the significant attributes for the purchase of milk. To know the relationship between family size, family income, qualification, and purchase preference of milk categories, chi-square test was conducted. The study found that taste, price, easy availability, and brand were the significant attributes for the purchase of packaged milk. It was found that family income and qualification played a very significant role in the consumers’ preference for the purchase of packaged milk. Factors such as packaging, quality, and safe for health were found to be the non-significant factors for the purchase decision of packaged milk. The study found that consumers perceived packaged milk to be more hygienic, safe, and of better quality